O-266 Multi-omics landscape of uterine fluid-derived extracellular vesicles across the menstrual cycle - Apostolov, A; Mladenovic, D; Baev, V; Yahubyan, G; Tilk, K; Görgens, A; Bergamelli, M; Kalinina, A; Saare, M; Lõhmus, A; Milov, A; Nikolova, M; et al. (HUMAN REPRODUCTION, 2024)
Abstract Study question Do extracellular vesicles (EVs) mirror the cyclic physiological changes in endometrial tissue, reflecting the endometrial maturation along the entire menstrual cycle? Summary answer Multi-omics data highlights the importance of EVs during the mid-secretory phase and EVs cargo reflects the state of the tissue throughout the menstrual cycle. What is known already Extracellular vesicles isolated from uterine fluid (UF) during the mid-secretory phase have been characterized for their pivotal role in embryo-maternal communication, particularly in the context of microRNAs (miRNAs) and mRNA. EVs have been posited as potential biomarkers in a minimally invasive liquid biopsy approach for assessing endometrial receptivity, hopefully replacing the endometrial tissue biopsy-based testing. However, the dynamics of EVs and their cargo throughout the distinct phases of the menstrual cycle remain unknown. This is the first study to elucidate UF-EV content throughout the maturation of the endometrium. Study design, size, duration Whole-exome RNA and small-RNA sequencing was performed on 15 paired samples, comprising UF and endometrial biopsy (EB), obtained from healthy female subjects across the menstrual cycle. This initial dataset was expanded with 35 additional UF samples. Cumulatively, the analysis encompassed samples (EB and UF) across the menstrual cycle’s four distinct phases: proliferative (n = 10), early-secretory (ES) (n = 17), mid-secretory (MS) (n = 20), and late-secretory (LS) (n = 18). Additionally, 20 UF-EV samples were used for flow cytometry surface proteome analysis. Participants/materials, setting, methods Participants were excluded when infertility-associated conditions were found and included when they had at least one child born, with no hormonal medications used for three months before the sampling. EVs were extracted from UF with size-exclusion chromatography (SEC) and subsequently with glycosaminoglycan-based precipitation. The EVs were characterized with nanoparticle tracking analysis, western blot, transmission electron microscopy and flow-cytometry surface proteome analysis (MACSPlex) for 37 surface markers. Single-end RNA and small-RNA sequencing were performed on NextSeq1000. Main results and the role of chance The transcriptome, miRNome, and protein surface markers of UF-EVs were characterized throughout the menstrual cycle. Transcriptome profiling was performed in comparison to the preceding phase. During the ES phase, 5,507 differentially expressed genes (DEGs) were observed, most of them being downregulated and associated with G-coupled-protein signaling, while in the MS phase, 867 DEGs were identified associated with nucleosome assembly and cell differentiation. Interestingly in the LS phase, the histone genes associated with nucleosome assembly were upregulated compared to MS, highlighting that histone dynamics change corresponding to the menstrual cycle. The exploration of gene ontology revealed consistent enrichment of genes related to extracellular vesicles in UF-EV and EBs across the menstrual cycle. The miRNA analysis of UF-EVs and EB showed significant overlap in miRNA expression level especially in the MS phase. Furthermore, we found 16 unique miRNAs in the mid-secretory phase whose targets were associated with embryo morphogenesis and cell adhesion. MACSPlex analysis revealed that CD9 and CD63, canonical EV markers, were significantly abundant during the MS phase, indicative of an enriched secretion of EVs during the preparation of the endometrium for embryo implantation. These insights underscore that the cargo of UF-EVs reflects the dynamic changes in the endometrial tissue. Limitations, reasons for caution The research on UF-EVs faced notable challenges due to the irregular and non-standardized collection methods of UF in gynecological practice. This variability in UF collection introduces potential confounding factors. The study also operated with a limited sample size, underscoring the need for further validation. Wider implications of the findings Our study indicates that the UF-EVs reflect the menstrual cycle-related molecular changes and UF-EV analysis could be potentially used to follow the menstrual cycle-related molecular processes in the uterine environment. Trial registration number not applicable